2019
DOI: 10.1016/j.astropartphys.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the origin of the gamma-ray emission in NGC 1068 with the Cherenkov Telescope Array

Abstract: Several observations are revealing the widespread occurrence of mildly relativistic wide-angle AGN winds strongly interacting with the gas of their host galaxy. Such winds are potential cosmic-ray accelerators, as supported by gamma-ray observations of the nearby Seyfert galaxy NGC 1068 with the Fermi gamma-ray space telescope. The non-thermal emission produced by relativistic particles accelerated by the AGN-driven wind observed in the circum-nuclear molecular disk of such galaxy is invoked to produce the gam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 81 publications
0
34
0
Order By: Relevance
“…The shaded gray band indicates the upper (p=2, E cut =6×10 6 GeV, and ξ=0.25) and lower (p=2, E cut =3×10 5 GeV, and ξ=0.2) bounds of the gamma-ray emission predicted by the AGN wind model as proposed by Lamastra et al (2016). For the sake of clarity, the predictions of the revised AGN wind model (Lamastra et al 2019) are not shown, as they do not differ from that by Lamastra et al (2016) at energies smaller than 10 TeV. For comparison, the spectrum predicted by the AGN wind model that is obtained by assuming one of the combinations of CR proton spectral parameters compatible with the MAGIC upper limits (p=2, E cut =8×10 3 GeV, and ξ=0.2, see Figure 3), is shown with the dark gray line.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The shaded gray band indicates the upper (p=2, E cut =6×10 6 GeV, and ξ=0.25) and lower (p=2, E cut =3×10 5 GeV, and ξ=0.2) bounds of the gamma-ray emission predicted by the AGN wind model as proposed by Lamastra et al (2016). For the sake of clarity, the predictions of the revised AGN wind model (Lamastra et al 2019) are not shown, as they do not differ from that by Lamastra et al (2016) at energies smaller than 10 TeV. For comparison, the spectrum predicted by the AGN wind model that is obtained by assuming one of the combinations of CR proton spectral parameters compatible with the MAGIC upper limits (p=2, E cut =8×10 3 GeV, and ξ=0.2, see Figure 3), is shown with the dark gray line.…”
Section: Resultsmentioning
confidence: 99%
“…Both processes contribute in turn to the uncertainty in the computation of p and E cut . As discussed in Lamastra et al (2019), absorption due to the EBL and to the infrared emission from the starburst ring surrounding the acceleration regions affects the gamma-ray spectrum only above E10 TeV, thus the constraints shown in Figure 3 can be considered robust.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of the energy dispersion matrix for sources requiring a detailed spectral treatment in the softer energies (e.g. E 500 GeV) and will be shown (Romano et al 2018;Lamastra et al 2019) to increase the run time by a factor of 5-10.…”
Section: Budget Discussionmentioning
confidence: 99%